Protecting Family Interests: An Interview Study with Foreign-Born Parents Struggling On in Childhood Cancer Care - Pernilla Pergert; Solvig Ekblad; Olle Björk; Karin Enskär; Tom Andrews (Hindawi Limited, 2012)
Sweden's population is gradually changing to become more multiethnic and diverse and that applies also for recipients of health care, including childhood cancer care. A holistic view on the sick child in the context of its family has always been a cornerstone in childhood cancer care in Sweden. The purpose of this study was to gain knowledge about the experiences and main concern of foreign-born parents in the context of paediatric cancer care. Interviews were performed with eleven foreign-born parents and data were analysed using a classic grounded theory approach. Foreign-born parents often feel in a position of powerless dependence, but family interests are protected in their approaches to interaction with healthcare staff, through cooperation, contesting, and reluctant resigning. Healthcare staff need to listen to foreign-born parents and deal with their concerns seriously to prevent powerless-dependence and work for trustful cooperation in the common fight against childhood cancer.